• 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 
 • 






,





: . : .. 3- :
1997 .
() .
, , ,

.
:
() x, :

ì -2/(2m)×2/x2 + U0 , x < -a
Ù ï
H = í -2/(2m0)×2/x2 , -a < x < a
ï
î -2/(2m)×2/x2 + U0 , x > a
m -
I , III ;
m0 -
II.

:
ì 2YI/x2 + 2m/2×(E - U0)YI = 0 ,
x £ -a
ï
í 2YII/x2 + 2m0/2×E×YI
= 0 , -a £ x £ a
ï
î 2YIII/x2 + 2m/2×(E - U0)×YI
= 0 , x ³ a
I :
1-
:
YI(x) =
A×exp(n×x) + B×exp(-n×x).
,
B = 0. ,
YI(x) =
A×exp(n×x).

:
YII(x) =
C×exp(i×k×x) + D×exp(-i×k×x).

:
YIII(x) =
F×exp(-n×x).

k =
(2m0×E/2)1/2
n = (2m×(U0-E)/2)1/2.

:
¨
4 ,
.
¨
4
A,C,D F.
.
¨ ,

. ,
,
.
, ..
:
YI(x=-a) = YII(x=-a)
YII(x=a)
= YIII(x=a)
YI¢(x=-a)/m = YII¢(x=-a)/m0
YII¢(x=a)/m0
= YIII¢(x=a)/m

:
A×exp(-n×a) = C×exp(-i×k×a) + D×exp(i×k×a)
m-1×A× n×exp(-n×a) = i×k×/m0×(C×exp(-i×k×a) - D×exp(i×k×a))
C×exp(i×k×a) + D×exp(-i×k×a) = F×exp(-n×a)
i×k×/m0×(C×exp(i×k×a) - D×exp(-i×k×a)) = - n/m×F×exp(-n×a).

:
|exp(-n×a) -exp(-i×k×a) -exp(i×k×a) 0 |
|m-1×n×exp(-n×a) -1/m0×i×k×exp(-i×k×a) 1/m0×i×k×exp(i×k×a) 0 |
|0 exp(i×k×a) exp(-i×k×a) -exp(-n×a) |
|0 1/m0×i×k×exp(i×k×a) -1/m0×i×k×exp(-i×k×a) 1/m×n×exp(-n×a)|

,
:
((n/m)2
- (k/m0)2)×Sin(2×k×a) + 2×k×n/(m×m0)×Cos(2×k×a) = 0.

, ,
.

A, C,
D, F .
,
.
C = F×exp(-n×a)×{exp(i×k×a) + exp(-3×i×k×a) ×( i×k/m0 - n/m)/(n/m + i×k/m0)}
D = C×exp(-2×i×k×a)×( i×k/m0 - n/m)/(n/m + i×k/m0)
A = exp(n×a)×(C×exp(-i×k×a) + D×exp(i×k×a)) .
A, C
D
F, :
A = RA×F
C = RC×F
D = RD×F.
RA, RC, RD -
.
,
- F,
A, C, D.
.

:
YI(x) =
F×RA×exp(n×x)
YII(x) =
F×( RC×exp(i×k×x) + RD×exp(-i×k×x)).
YIII(x) =
F×exp(-n×x).
I1 + I2 + I3 = 1

I1 = |F|2×|RA|2×òQexp(2×n×x)×dx = |F|2×|RA|2×(2×n)-1×exp(2×n×x) =
= |F|2×|RA|2×(2×n)-1×exp(-2×n×a)
I2 = |F|2×RC = |F|2×+ i×((exp(-2×i×k×a) - exp(2×i×k×a))×RC*×RD/(2×k)
I3 = |F|2×òWexp(-2×n×x)×dx = |F|2×(2×n)-1×exp(-2×n×a)
|F|2 = ((exp(2×i×k×a) - exp(-2×i×k×a))×RC×RD*/(2×i×k) +
-1.
,
F,
A, C, D, ,
.


,
, ,
. .
,
.
, ,
.

:
U(x)=U(x+2a) (1)
(1)
,
.
, ,
I, III,
:
2Y/x2 + 2m/2×(E - U0)Y = 0

, .

:
r =
exp(i 2ak)
Y(x+2ma) = Y(x)×rm ,
m=0, 1,
2,... (2)
,
(
E<U0)
I, II, III. , (2),
.
I:

:
2YI/x2 + 2m2/2×(E - U0)YI = 0
, 0 > x > -a

:
YI(x) =
A×exp(n×x) + B×exp(-n×x).
n = (2m2
(U0-E)
/2)1/2
II:

:
2YII/x2 + 2m1/2×E YII = 0 , a ³ x ³ 0

:
YII(x) =
C×exp(i×p×x) + D×exp(-i×p×x).
p = (2m1E/2)1/2
III:
2YIII/x2 + 2m2/2×(E - U0)YIII = 0
, 2a > x > a

:
YIII(x) = r (A×exp(n×x) + B×exp(-n×x)).
:
YI(x=0) = YII(x=0)
YII(x=a)
= YIII(x=a)
YI¢(x=0)/m = YII¢(x=0)/m0
YII¢(x=a)/m0
= YIII¢(x=a)/m

,
A, B, C, D:
A+B=C+D
C exp(i p a)+D exp(-i p a) = exp(i 2 a k) (A
exp(n a)+B exp(-n a))
(A-B)
n/m2 = (C-D) i p / m1
(C
exp(i p a)-D exp(-i p a)) i p / m1 = exp(i 2
a k) n/m2 (A exp(n a)-B exp(-n a))

, :
|1 1 -1 -1 |
|exp(i×k×2a+n×a) exp(i×k×2a-n×a) -exp(i×p×a) -exp(-i×p×a) |
|n/m2 -n/m2 -i×p/m1 i×p/m1 |
|n/m2exp(i×k×2a+n×a) -n/m2×exp(i×k×2a-n×a) -
i×p/m1×exp(i×p×a) i×p/m1×exp(-i×p×a) |
.


.

.
a=10; U=10; m1=4; m2=1
0.1135703312666857 0.6186359585387896 0.2019199605676639 0.3155348518478819 0.05047267055441365 1.263391478912778 0.4544326758658974 2.137353840637548 0.808172718170137 2.479933076698526 0.4544326758658974 6.168062551132728 5.611693924351967 1.820461802850339 1.529165865668653 1.023077302091622

a=10 U=10 m1=2 m2=1
0.1032788024178655 0.2324238959628721 0.41331603936642 0.6460490460448886 0.930750939555283 1.26759057783714 1.656787195799296 2.098624192369327 2.593469359607937 3.141805331837109 3.744277072860902 5.887485640841992
a=10 U=10 m1=1 m2=1 0.05408120469105441 0.2163802958297131 0.4870681554965061 0.86644533469418 1.354969224117534 1.953300729714778 2.662383817919513 4.418966218448088 7.961581805911094

a=10 U=10 m1=0.5 m2=1 0.118992095909544 4.249561710930034 1.068004282376146 0.4754473139332004 5.78216724725356 2.955345679469631 1.895012565781256
a=10 U=10 m1=.25 m2=1 0.2898665804439349 4.30026851446248 2.479039415645616 1.132264393019809

      ©2010